Salzmann nodular degeneration: prevalence, impact, and management strategies - Paranjpe V (Dove Medical Press, 2019)
Vikram Paranjpe,1 Anat Galor,1,2 Pedro Monsalve,1 Sander R Dubovy,1 Carol L Karp11Department of Ophthalmology, University of Miami Miller School of Medicine, Miami, FL 33136, USA; 2Department of Ophthalmology, Miami Veterans Administration Medical Center, Miami, FL 33125, USAPurpose: This review will summarize the clinical and histological presentation of Salzmann nodular degeneration (SND), its prevalence and risk factors, potential underlying mechanisms, diagnostic tools, management options, and impact on cataract surgery and co-morbid ocular surface diseases.Method: PubMed review of 44 articles published between 1976 and 2018.Results: SND is a corneal disease characterized by whitish gray or bluish nodules on the peripheral or central cornea. The clinical presentation of SND is variable and the nodules can be asymptomatic or cause foreign body sensation and/or blurred vision. Histologically, SND appears as subepithelial nodules with thin overlying epithelium, disrupted or absent Bowman’s layer, and activated fibroblasts within the nodule. SND pathogenesis is not fully understood but is thought to involve poor epithelial protection and disruption of the epithelial–stromal interface, allowing for penetration of epithelially derived growth factors into the stroma and subsequent activation of stromal fibroblasts, eventually leading to sub-epithelial deposition of disorganized extracellular membrane components. SND most commonly occurs in Caucasian females in a bimodal distribution, occurring in the fifth or eighth and ninth decades of life. Risk factors for SND include ocular surface diseases and surgery. Surgical intervention is recommended in individuals with symptomatic nodules – primarily superficial keratectomy performed with or without intraoperative mitomycin C, photokeratectomy, and/or amniotic membrane transplantation. These procedures have been successful in removing the lesion and reducing corneal irregularity, but have variable recurrence rates (0–31%).Conclusion: The pathogenesis of SND is complex and multifactorial. Advances in diagnostic and treatment modalities have allowed for earlier and more accurate diagnosis and effective treatment of SND. Keywords: Salzmann nodular degeneration, cornea, diagnosis, imaging, treatment